An Analysis of the Effects of Uncertainty and Irreversibility on Farmer Participation in the Conservation Reserve Program - Murat Isik; Wanhong Yang (Journal of Agricultural and Resource Economics, 2004)
A real options model is developed to examine the determinants of farmer participation in the Conservation Reserve Program (CRP). This study contributes to the literature by developing a framework for ex post analysis of uncertainty and irreversibility. It extends the applications of real options models to analyze farmer participation in the CRP. The model incorporates land and owner attributes, and determines whether uncertainty and irreversibility affect the probability of participation. Option values play a significant role in farmer decisions to retire land by reducing the probability of participation. These results have implications for the design and implementation of conservation programs.